Research on the Development of Smart Home Based on Multi-Perspectives. Issue 3 (April 2020) - Wang, Yujie; Liao, Zhipeng; Shen, Yongluo
Abstract: With the continuous growth of China's emerging industries, the digital life of Chinesehas ushered in a new era, and smart home has a huge market and user value. In order to provide a reference for the theoretical research of smart home, and help the application and development of the important concept of "smart+" wasfirst proposed in the 2019 government work report.Through systematic review of domestic and foreign literature on smart home, the reasons for the rapid development are summarized from the functional and social technology perspective. The challenges faced in the development are summarized from the user's point of view. The trend of smart home development is summarized from the perspective of industry and society.